Evaluation of the risk relationship between average alcohol volume consumed and suicide in the USA: an analysis of mortality linked cohort data - Lange, Shannon; Zhu, Yachen; Probst, Charlotte (Injury prevention, 2024)
Objective Alcohol use disorder is an established risk factor for suicide; however, it is largely unknown whether subclinical levels of drinking may also contribute to the risk of suicide. The objective was to evaluate the relationship between average alcohol volume consumed per day and suicide. - Methods Data from the annual, cross-sectional National Health Interview Survey, 1997-2018 in the USA, was obtained and linked to the 2019 National Death Index. The association between average alcohol volume consumed in grams per day (g/day) and suicide was quantified using Cox proportional hazards model (multiplicative) and Aalen’s additive hazard model. All analyses were stratified by sex, and adjusted for education, marital status, psychological distress, race and ethnicity, and survey year. - Results On the multiplicative scale, for males, former drinkers and those who consumed on average >40-60 g/day had about 43% (HR=1.43, 95% CI 1.03, 2.01) and 72% (HR=1.72, 95% CI 1.14, 2.60) greater risk of dying by suicide, compared with lifetime abstainers, respectively. There was no significant association found for former or current drinkers among females, on the multiplicative scale. On the additive scale, for males, drinking >40-60 g/day on average was associated with 22.7 (95% CI 6.0, 39.4) additional deaths per 100 000 person-years, while for females, being a former drinker and drinking >0-20 g/day on average was associated with 5.5 (95% CI 0.7, 10.4) and 1.9 (95% CI 0.2, 3.5) additional deaths per 100 000 person-years, compared with lifetime abstainers. The level of education was not found to modify the focal relationship for males or females. - Conclusions The findings suggest that the relationship between average alcohol volume consumed per day and suicide is nuanced. Additional research on the respective relationship is needed, including repeated measures of average alcohol consumption over time.